2021
DOI: 10.3390/su132111972
|View full text |Cite
|
Sign up to set email alerts
|

The Maturity of Corporate Websites as a Digital Communication Channel in Portuguese SMEs’ Process of Adopting E-Commerce

Abstract: This study aims to determine the maturity of the websites of Portuguese small and mid-sized enterprises (SMEs) as a basic form of digital communication in the sequential process of incorporation of e-commerce. The starting premise is that there is a relationship between the level of maturity reached in the SMEs’ websites as digital tools that allow firms to communicate effectively, and the adoption of e-commerce. To study this, a representative sample of 381 SMEs located in Portugal and selected through strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
2
0
4
Order By: Relevance
“…Corporate websites are a basic tool in the digitalization process of companies and fundamental for digital communication (García-García et al 2021). As Saleem et al (2022) concluded in their research, a quality corporate website with clear, concise, engaging and relevant content for the audience positively influences consumers' purchasing decisions and consequently benefits the financial performance of the business.…”
Section: Digitalization Of the Restaurant Industry During Covid-19 An...mentioning
confidence: 99%
“…Corporate websites are a basic tool in the digitalization process of companies and fundamental for digital communication (García-García et al 2021). As Saleem et al (2022) concluded in their research, a quality corporate website with clear, concise, engaging and relevant content for the audience positively influences consumers' purchasing decisions and consequently benefits the financial performance of the business.…”
Section: Digitalization Of the Restaurant Industry During Covid-19 An...mentioning
confidence: 99%
“…El emica es una metodología para evaluar sitios web de forma secuencial, que analiza el proceso de comunicación bajo el esquema de información-interacción-acción, en el que se representa el proceso funcional que debe completar cada sitio web (García-García et al, 2021). Luego de que una organización se establece en la red, desarrolla funciones de forma paulatina de acuerdo con su experiencia en el uso del Internet, razón por la que este modelo es usado para medir el grado de implementación y madurez del comercio electrónico en las empresas.…”
Section: Modelo Extendido Para La Implementación Del Comercio Electró...unclassified
“…Esta etapa presenta uno de los porcentajes más bajos dentro de las etapas ya mencionadas, en la que el 54% de las organizaciones cumplían con esta etapa. Sin embargo, la falta de este nivel no es reflejo de la ausencia del comercio electrónico, ya que algunas organizaciones adoptan el comercio electrónico, aunque no lo hagan tomando como referencia la secuencia del modelo (García-García et al, 2021). Para la mejora del posicionamiento de las organizaciones en la web, se debe proporcionar al internauta la facilidad del pago en línea, con el fin de generar confianza, competitividad y entrada exitosa a los mercados (Kharat & Nagare, 2021).…”
Section: /5unclassified
“…En el escenario pospandémico, el punto de partida fundamental para las pequeñas y medianas empresas es su capacidad para sobrevivir, adaptarse y adoptar nuevos modelos de negocio (Costa & Castro, 2021). Es evidente que la supervivencia en la economía digital requiere que estas empresas adapten e integren nuevas herramientas de comunicación digital en sus modelos de negocio (García et al, 2021).…”
Section: Introductionunclassified